Methylome changes in Lolium perenne associated with long-term colonisation by the endophytic fungus Epichloë sp. LpTG-3 strain AR37 - Forte, Flavia Pilar; Malinowska, Marta; Nagy, Istvan; Schmid, Jan; Dijkwel, Paul; Hume, David E.; Johnson, Richard D.; Simpson, Wayne R.; Asp, Torben (Frontiers in Plant Science, 2023)
Epichloë spp. often form mutualistic interactions with cool-season grasses, such as Lolium perenne, but the molecular mechanisms underlying this interaction are poorly understood.Reduced representation bisulfite sequencing was used to investigate the impact of the Epichloë sp. LpTG-3 strain AR37 on the methylome of L. perenne across multiple grass generations and under drought stress conditions.Results showed that the presence of the endophyte caused a decrease in DNA methylation across genomic features, with differentially methylated regions primarily located in intergenic regions and CHH contexts. The presence of the endophyte affected the methylation profile differently across generations, with endophyte-positive plants being consistently hypomethylated.This study sheds new light on the molecular mechanisms underlying the mutualistic interaction between Epichloë sp. LpTG-3 strain AR37 and L. perenne, specifically highlighting the role of methylation changes associated with the endophyte infection. The findings suggest that the global DNA hypomethylation observed in L. perenne may be influenced by endophyte-plant association length and other genetic and epigenetic factors accumulating over time. This is a provisional file, not the final typeset article symbionts (Christensen et al., 1997;Gagic et al., 2018). When not pathogenic, the fungus is exclusively transmitted to the next generation through seed (Philipson and Christey, 1986). Endophyte-host interactions play a crucial role in plant growth and development and in the response of infected plants to stressors (Schardl and Leuchtmann, 2005).When in a mutualistic relationship with their host plants, endophytes like Epichloë sp. can provide numerous benefits to the host, including protection against biotic and abiotic stressors (